The Understanding Customer Satisfaction on Internet Banking: A Case Study in Indonesia - Ronny; Nurhadi, Mochamad; Ilfitriah, Aniek Maschudah (LPPM Universitas Terbuka, 2020)
The study aims to understand the factors contributing to satisfaction when using internet banking services. This research was carried out by using a qualitative and quantitative approach, as it is intended to analyze the results of banking marketing. Data were collected by filling out questionnaires from 120 respondents who used internet banking of banks in Indonesia. Besides, a focus group discussion was conducted to deepen the factors which contribute to customer satisfaction. Findings. The results indicated that convenience and reliability are factors that can quickly and accurately reduce customers’ dissatisfaction and inconvenience. The reliability factor is the main cause of customer dissatisfaction in using internet banking (52.08%), while convenience is the major factor leading to customer satisfaction (61.07%). Customer segments have influenced the customer's expected priority of choosing Internet banking services.